2003
DOI: 10.1161/01.cir.0000081770.51929.5a
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Biochemical Evaluation of Platelet Aspirin Resistance After Coronary Artery Bypass Surgery

Abstract: Background-Aspirin inhibits platelet activation and reduces atherothrombotic complications in patients at risk of myocardial infarction and stroke. However, a sufficient inhibition of platelet function by aspirin is not always achieved. The causes of this aspirin resistance are unknown. Methods and Results-Patients undergoing coronary artery bypass grafting (CABG) have a high incidence of aspirin resistance. To evaluate functional and biochemical responses to aspirin, platelet-rich plasma was obtained before a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
194
1
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(211 citation statements)
references
References 25 publications
9
194
1
7
Order By: Relevance
“…Our results showed that aspirin appears to be effective in reducing VTE after cardiac surgery in the pediatric population (using 5 mg/kg/day)45 or when a higher dose of aspirin is used in adults (>300 mg/day) 68. Evidence suggests that aspirin resistance is common within the first week after cardiac surgery and the standard low‐dose aspirin (100 mg/day) would not be adequate to exert its full antiplatelet effects in many patients 11, 12, 13. Because cardiac surgical patients are also prothrombotic postsurgery (up to 30 days),6, 7, 8, 9 use of low‐dose antiplatelet agents alone would not be sufficient in preventing VTE during this high‐risk period if the patients have multiple risk factors for VTE (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that aspirin appears to be effective in reducing VTE after cardiac surgery in the pediatric population (using 5 mg/kg/day)45 or when a higher dose of aspirin is used in adults (>300 mg/day) 68. Evidence suggests that aspirin resistance is common within the first week after cardiac surgery and the standard low‐dose aspirin (100 mg/day) would not be adequate to exert its full antiplatelet effects in many patients 11, 12, 13. Because cardiac surgical patients are also prothrombotic postsurgery (up to 30 days),6, 7, 8, 9 use of low‐dose antiplatelet agents alone would not be sufficient in preventing VTE during this high‐risk period if the patients have multiple risk factors for VTE (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The same effect can be progressively achieved with the chronic administration of daily doses of 30 to 50 mg. 1 COX has 2 isoforms with different tissue distribution and susceptibility to inhibition by NSAID. COX-2 in not inhibited by therapeutic doses of aspirin and, under physiological conditions, is present in a small fraction of platelets, [3][4][5] but the number of COX-2-expressing platelets may increase in conditions of high platelet regeneration. 5 Because aspirin acetylates COX-1 in all tissues, including endothelial cells, where the enzyme converts arachidonic acid into the vasodilator and natural platelet antagonist prostacyclin, for several years there has been the concern that the potential antithrombotic effect of aspirin could be blunted, or even overcome, by the theoretical prothrombotic effect associated with the parallel inhibition of prostacyclin.…”
Section: Aspirinmentioning
confidence: 99%
“…The relative ineffectiveness of aspirin as an anti-inflammatory drug is mirrored at the cellular level by the demonstration that aspirin is 166 times more potent in inhibiting PGHS activity in the platelet than in the J774.2 macrophage cell line [8], leading to consideration that the action of aspirin might be selective for the PGHS-1 isoform. However, the potency of inhibition of PGHS-1 by aspirin ex vivo observed in normal platelets is lost in platelets of patients after coronary artery bypass grafting [9], and PGHS-1 from platelet homogenates is poorly acetylated by aspirin [10], suggesting differences in acetylation that can not be attributed to isoform selectivity. Collectively, these observations reflect considerable variability in acetylation of the PGHSs by aspirin, a variability that implies a mechanistic basis for regulating the action of the drug.…”
Section: Introductionmentioning
confidence: 99%